PERTUMBUHAN BIBIT KAKAO (Theobroma cacao L.) YANG DITANAM PADA BEBERAPA MEDIUM TUMBUH DENGAN PEMBERIAN PUPUK ORGANIK CAIR - Klaus Rotama Ginting; Gunawan Tabrani; Sukemi Indra Saputra (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
This research aimed to produce good Cacao (Theobroma cacao L.) seedlings, which is planted on on some grows medium by giving organic liquid fertilizer. This research was conducted at Agriculture Faculty of Riau University, Pekanbaru, on 10 m above of the sea. Started from April to September 2014. This research used Factorial Completely Randomized Design (CRD) with two factors and three replictions. Factror I: grows medium with 3 levels, M1: Inceptisol soil, M2: Red Yellow Podzolik soil and M3: Peat soil. Factor II: concentration of organic liquid fertilizer with 3 levels, O1: 0%, O2: 0,78% and O3: 1,56%. Parameters observed were the seedlings height, stem diameter, number of leaves and leave area. The result showed that the use of some grows medium and the organic fertilizer affect the growth of Cacao seedlings. But interaction between both of treatment not affect the growth of Cacao seedlings. The combination of organic liquid fertilizer concentration 1,56% with Inceptisol soil tended to increase seedlings height and stem diameter, while the combination of organik liquid fertilizer concentration 1,56% with Peat soil tended to increase number of leaves and leave area. Keywords: Cocoa seedlings, grows medium, organic liquid fertilizer